2014
DOI: 10.1136/gutjnl-2014-307453
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms atPRSS1–PRSS2andCLDN2–MORC4loci associate with alcoholic and non-alcoholic chronic pancreatitis in a European replication study

Abstract: The single-nucleotide polymorphisms rs10273639 at the PRSS1-PRSS2 locus and rs7057398 and rs12688220 at the CLDN2-MORC4 locus are associated with CP and strongly associate with ACP, but only rs7057398 with NACP in female patients.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 20 publications
5
97
1
1
Order By: Relevance
“…In contrast, risk variants of other genes typically confer smaller but significant risk and are often found in the transheterozygous state in affected carriers (25). More recently, a GWAS study identified common variants in the CLDN2 locus and in the promoter region of PRSS1 that appear to increase disease risk only by a small degree (10,43).…”
mentioning
confidence: 99%
“…In contrast, risk variants of other genes typically confer smaller but significant risk and are often found in the transheterozygous state in affected carriers (25). More recently, a GWAS study identified common variants in the CLDN2 locus and in the promoter region of PRSS1 that appear to increase disease risk only by a small degree (10,43).…”
mentioning
confidence: 99%
“…Mutations in this gene have been associated with chronic pancreatitis particularly in those individuals who consume alcohol. It has recently been described to be involved in pancreatic acinar cells [40]. And finally, the gene CPA1 encodes a pancreatic digestive enzyme whose mutations have been found to be involved in early onset of chronic pancreatitis.…”
Section: Gene (S) Involved Clinical Featuresmentioning
confidence: 99%
“…Genomic DNA will be isolated and genetic analyses of the cationic trypsinogen (PRSS1) [16,17,18,19], chymotrypsin C (CTRC) [20,21], cystic fibrosis transmembrane conductance regulator (CFTR) [22], serine peptidase inhibitor Kazal type 1 (SPINK1) [23,24], carboxypeptidase A1 (CPA1) [25] and carboxyl-ester lipase (CEL) [26] will be performed. In order to detect the most common mutations concerning PRSS1 (p.A16V, p.N29I, p.R122C and p.R122H) exon-2 and exon-3, concerning CPA1 mutations (p.V251M, p.N256K, p.Y308H and p.R382W) exon-7, exon-8 and exon-10, concerning SPINK1 (p.N34S and c.194+2T>C) exon-3, concerning CTRC (p.G60G, p.V235I, p.R254W and p.K247_R254del) exon-3 and exon-7, concerning CFTR (p.R117H and p.F508del) exon-4 and exon-11 and concerning CEL all exons will be sequenced.…”
Section: Methodsmentioning
confidence: 99%